Analisis Pencantuman Klausula Eksonerasi Dalam Perjanjian E-Commerce Menurut Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Devinda Diana Valentina; Suraji Suraji (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This research examines the validity of agreements regarding the inclusion of exoneration clauses in e-commerce transactions. Agreements between marketplace companies and their users are packaged in the form of standard agreements. This allows for the inclusion of eksonerasi clauses containing exoneration elements that may harm users. The research method used by the Author is normative legal research with a prescriptive nature. The types and sources of research data include primary data consisting of legislation, basic principles, jurisprudence, and other fundamental regulations, as well as secondary data obtained through literature review. Based on the research findings, the use of standard agreements is generally allowed as long as it does not violate Article 18 paragraph (1) of the Consumer Protection Law. Such violation constitutes a breach of the conditions for the validity of the agreement in terms of a lawful cause, thus rendering the use of exoneration clauses legally void.